Coping mechanism against high levels of daily stress by working breastfeeding mothers in Iran - Sousan Valizadeh; Mina Hosseinzadeh; Eesa Mohammadi; Hadi Hassankhani; Marjaneh M. Fooladi; Allison Cummins (Elsevier, 2018)
Objectives: Breastfeeding mothers returning to work undertake multiple conflicting roles at home and work that can result in high levels of stress. Exploring coping skills amongst these mothers can help in planning useful programmes to promote family wellbeing. This study aims to explore the experiences of working breastfeeding mothers and their coping mechanism against high levels of daily stress. Methods: In this qualitative study, we described the experiences of 20 Iranian breastfeeding mothers through in-depth and semi-structured interviews. All interviews were recorded, transcribed and analysed using thematic analysis. Results: Two main themes emerged as follows: 1) self-management with subthemes of a) attitude reconstruction, b) order and planning, c) creating a boundary between work and family and d) reprioritising life affairs; and 2) seeking help with subthemes of a) family member support, b) childcare facilities and c) spirituality. Conclusions: Findings suggest that women need support from family members and family-friendly policies at the workplace. Breastfeeding mothers may benefit from educational programmes that focus on effective coping strategies. Keywords: Breastfeeding, Coping, Employment, Iran, Stress, Women's health